2019
DOI: 10.3390/en12224235
|View full text |Cite
|
Sign up to set email alerts
|

Clean Poultry Energy System Design Based on Biomass Gasification Technology: Thermodynamic and Economic Analysis

Abstract: Despite growing attention has been paid to waste material gasification for high-efficiency energy conversion, the application of gasification technology in meat waste management is still limited. To fill this gap, this study designed two systems which evaluated the potential of using gasification technology to manage the poultry waste that has been exposed to highly pathogenic avian influenza (HPAI). Two systems are simulated by using Aspen plus combined with a one-dimensional kinetics control gasification mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…To investigate the economic feasibility of this approach, some studies have estimated the cost of energy recovery from poultry waste. For instance, Zang et al ( 2019) estimated that the variable operating cost of poultry gasification systems is about 477 US dollars per ton, which is 30 US dollars lower than that of poultry drying systems, and the poultry gasification system seems to show better certainty than the poultry drying system in terms of economic performance [110]. However, this study also indicated that labor costs and variable factors can greatly affect the waste elimination cost [110].…”
Section: Economic Benefitsmentioning
confidence: 73%
See 2 more Smart Citations
“…To investigate the economic feasibility of this approach, some studies have estimated the cost of energy recovery from poultry waste. For instance, Zang et al ( 2019) estimated that the variable operating cost of poultry gasification systems is about 477 US dollars per ton, which is 30 US dollars lower than that of poultry drying systems, and the poultry gasification system seems to show better certainty than the poultry drying system in terms of economic performance [110]. However, this study also indicated that labor costs and variable factors can greatly affect the waste elimination cost [110].…”
Section: Economic Benefitsmentioning
confidence: 73%
“…Therefore, some scholars have designed waste-to-energy systems based on the gasification process to process poultry waste. For instance, Zang et al (2019) designed two systems for poultry waste disposal and evaluated and compared their economic and energy potentials [110]. De Priall et al ( 2022) investigate the potential of energy recovery from poultry litter wastes with gasification systems based on feedstock analysis, process modeling, and experimental analysis [61].…”
Section: Gasificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different techniques and technologies [1], such as anaerobic digestion [2,3], hydrogenation, pyrolysis, and gasification [4,5], can be used for energy recovery and for the reduction of secondary products of poultry farms. In rural areas of Europe, biogas plants using biomass and animal waste are often found [6,7].…”
Section: Introductionmentioning
confidence: 99%